Comparison of Neurovascular Coupling between Normal Tension Glaucoma Patients and Healthy Individuals with Laser Speckle Flowgraphy. (1st November 2020) - Mursch-Edlmayr, A.S.; Pickl, L.; Calzetti, G.; Waser, K.; Wendelstein, J.; Beka, S.; Aranha dos Santos, V.; Luft, N.; Schmetterer, L.; Bolz, M.
ABSTRACT: Background : The purpose of this pilot study was to investigate the differences in neurovascular coupling between Caucasian patients with normal tension glaucoma (NTG) and healthy subjects (HS) with laser speckle flowgraphy (LSFG). Methods : Measurement of optic nerve head blood flow was performed with LSFG. The mean blur rate of the whole optic nerve head (MA), of the big retinal vessels (MV) and of the microvasculature (MT) was analysed during continuous flicker light stimulation for four minutes. Results : We included 12 eyes from 12 Caucasian patients with a diagnosis of normal tension glaucoma and 12 eyes from 12 age- and sex-matched healthy individuals. MA, MV and MT all increased significantly in both groups during the observation period with no difference between the groups. Conclusion : Neurovascular coupling is detectable in NTG patients. Flicker light stimulation leads to a comparable increase in ocular blood flow in glaucoma patients and healthy individuals.